Indigenous isiZulu Music in Transition: A Systematic Review and Linguistic Perspective on Its Cultural and Educational Significance - Yende, Sakhiseni Joseph (Forum for Linguistic Studies, 2025)
Indigenous isiZulu music represents a vibrant oral tradition through which the linguistic, cultural, and spiritual heritage of Zulu-speaking communities is preserved and transmitted. Yet, in the context of contemporary South Africa, its role is undergoing significant transformation due to rapid urbanisation, globalisation, and the continued marginalisation of indigenous knowledge within formal education systems. This study undertakes a systematic literature review (SLR) of 41 peer-reviewed sources published between 2000 and 2024, encompassing the fields of ethnomusicology, linguistics, and education. Following PRISMA guidelines, the review is grounded in Critical Indigenous Theory, Sociolinguistics, and Decolonial Pedagogy to investigate how isiZulu music contributes to identity construction, language preservation, and educational development. The review identifies four key thematic areas: (1) the continuity and adaptation of cultural practices, (2) the role of isiZulu music in the linguistic transmission of indigenous knowledge, (3) the exclusion of indigenous music from formal curricula, and (4) the emergence of hybrid musical forms among Zulu youth. The findings affirm the enduring relevance of isiZulu music in sustaining heritage and promoting linguistic vitality but also reveal systemic barriers, including a lack of policy support and limited teacher training. These limitations hinder the effective integration of indigenous content in school curricula. The study recommends the inclusion of isiZulu music within the Creative Arts curriculum, stronger partnerships between schools and indigenous knowledge holders, and the development of culturally responsive education policies. By positioning isiZulu music as a valuable linguistic and pedagogical asset, the review contributes meaningfully to debates on curriculum transformation and decolonisation in South African education.